Polarization‐Sensitive and Broadband Photodetection Based on a Mixed‐Dimensionality TiS3/Si p–n Junction. Issue 19 (25th July 2018) - Niu, Yue; Frisenda, Riccardo; Flores, Eduardo; Ares, Jose R.; Jiao, Weicheng; Perez de Lara, David; Sánchez, Carlos; Wang, Rongguo; Ferrer, Isabel J.; Castellanos‐Gomez, Andres
Abstract: The capability to detect the polarization state of light is crucial in many day‐life applications and scientific disciplines. Novel anisotropic 2D materials such as TiS3 combine polarization sensitivity, given by the in‐plane optical anisotropy, with excellent electrical properties. Here, the fabrication of a monolithic polarization‐sensitive broadband photodetector based on a mixed‐dimensionality TiS3 /Si p–n junction is demonstrated. The fabricated devices show broadband responsivity up to 1050 nm, a strong sensitivity to linearly polarized illumination with difference between the two orthogonal polarization states up to 350%, and a good detectivity and fast response time. The discussed devices can be used as building blocks to fabricate more complex polarization‐sensitive systems such as polarimeters. Abstract : A mixed‐dimensionality TiS3 /Si p–n junction with polarization‐sensitive and broadband photodetection is designed and fabricated. The heterostructure device shows a broadband responsivity from 405 to 1050 nm and a high sensitivity to polarized infrared illumination photodetection. The polarized contrast between b ‐ and a ‐axis directions of the TiS3 lattice is up to 350%.